Local Governments and the Financial Crisis : An Analysis - Paulais, Thierry (Cities Alliance, Washington, DC, 2013)
The financial and economic crisis that started in the United States has finally impacted all urban communities and investment financing systems around the world. Local governments grappling with the crisis face a number of constraints which, though disparate in nature, have a cumulative effect. This phenomenon has created a number of extremely difficult situations. In general terms, the consequences of the crisis can be felt on four levels: 1) revenue-either generated by local governments or derived from State transfers-which may be subject to sharp declines; 2) expenditures, which are rising because of the slowdown in economic activity and the corresponding increases in unemployment and social welfare needs; 3) financing capacities, which are shrinking owing to the difficulty in obtaining loans and the increase in the cost of money; and 4) foreign investment, which has declined; operations underway, which have been put on hold in many instances; and projects, which have either been cancelled or delayed. The two major financing systems bond issues and banks whether specialized or not, have been heavily impacted. Governments have adopted different measures depending on political and institutional environment. The situation differs greatly from one country to another. In some institutional contexts, local governments are relatively sheltered while in others, they are exposed. In terms of assets, local governments that can invest their funds in the market have been directly affected by losses in capital. The deterioration in local government accounts is often one of the factors constraining the ability of these governments to borrow.